Fabrication of Dye Sensitized Solar Cell (DSSC) Using Combination of Dyes Extracted from Curcuma (Curcuma xanthorrhiza) Rhizome and Binahong (Anredera cordifolia) Leaf with Treatment in pH of the Extraction - Pirim Setiarso; Rifanda Viantiano Harsono; Nita Kusumawati (Universitas Gadjah Mada, 2023)
Research on Dye Sensitized Solar Cell (DSSC) fabrication has been carried out using a combination of dyes extracted from Curcuma xanthorrhiza and Anredera cordifolia. Each dye was extracted by treating pH 1 to 13 and then characterized using UV-Vis spectroscopy. The band gap energy was determined by using the cyclic voltammetric method. The UV-Vis spectrum of C. xanthorrhiza extract reveals the presence of curcumin components. The UV-Vis spectrum of A. cordifolia indicates the presence of chlorophyll and a trace of anthocyanin. C. xanthorrhiza extract had the least band gap energy in the acid phase, pH 1, at 0.66 eV, and the alkaline phase, pH 13, at 0.43 eV. The minimum band gap energy of A. cordifolia extract was determined to be 0.96 eV in the acid phase, pH 7, and 0.65 eV in the alkaline phase, pH 12. When A. cordifolia and C. xanthorrhiza extracts were mixed, with the best composition ratios being pH 7:pH 1 (3:2 ≈ pH 1.7) and pH 12:pH 13 (1:4 ≈ pH 12.6). The composition of this mixture was applied to the DSSC resulting in an efficiency of 0.096 and 0.147%, respectively.